2010
DOI: 10.1002/jccs.201000099
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Liquid Chromatography Assay for Moxifloxacin in Bulk, Pharmaceutical Formulations and Serum: Application to In‐Vitro Metal Interactions

Abstract: A simple reversed phase HPLC method have been successfully developed and validated for the quantitative determination of moxifloxacin (MOX) in bulk material, pharmaceutical formulation and serum. Purospher STAR C18 (25 cm × 4.6 mm, 5 μm) and Discovery C18 (25 cm × 4.6 mm, 5 μm) columns were used. The mobile phase, methanol: acetonitrile: water (85:5:10, v/v/v), pH 2.75 adjusted by phosphoric acid was delivered at a flow rate of 1 mL min−1. The eluents was monitored using UV detector at 290 nm. The proposed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The results show that buffer of 0.06 N HCl was the best dissolution medium, the immediate release of hard gelatin capsule was 100% highest drug release and the disintegration time for the capsule was 15 minute. The rotation speed 75 or 100 rpm was adjusted for capsules (Table 1) [14], and the percentage of drug discharge was calculated with the help of statistical parameter Student's-t distribution test at 0.05 significant levels and the most interesting thing is that the both stirring speeds are practicable and functional for both products for 75 mg and for 150 mg capsules".…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that buffer of 0.06 N HCl was the best dissolution medium, the immediate release of hard gelatin capsule was 100% highest drug release and the disintegration time for the capsule was 15 minute. The rotation speed 75 or 100 rpm was adjusted for capsules (Table 1) [14], and the percentage of drug discharge was calculated with the help of statistical parameter Student's-t distribution test at 0.05 significant levels and the most interesting thing is that the both stirring speeds are practicable and functional for both products for 75 mg and for 150 mg capsules".…”
Section: Resultsmentioning
confidence: 99%
“…These all were quite exclusive methods because of their extended and monotonous pretreatment of the samples, extraction with solvent and derivatization for the analysis of pregabalin. Our research group has reported a number of LC methods for the determination of various drugs as quinolones [13][14][15], cephalosporines [16], Ca channel blockers [17], ACE inhibitors [18][19][20][21] and antidiabetic drugs [22][23][24][25][26][27]. In continuation with this work we report are rapid, sensitive, selective, precise, short time analysis and cost effective RP-HPLC method for the quantitation of pragabalin in API, dosage formulations and human serum, the method is being validated according to ICH guidelines [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The methods employed in the literature include high-Performance Liquid Chromatography (20,21) ; square-wave voltammetry by interaction of MOX with Cu(II) (6) ; potentiometric and UV spectrophotometric measurements through complex formation with gadolinium(III) ion (22) . Recently, MOX-copper complexes were synthesized, characterized and screened for anti-proliferative and apoptosis-inducing activity against multiple human breast cancer cell lines (23) .…”
Section: Fig1 Structure Of Moxifloxacinmentioning
confidence: 99%
“…Moxifloxacin (1-cyclopropyl-7-[(1S, 6S)-2, 8-diazabicyclo[4.3.0]non-8-yl]-6-fluoro-8-methoxy-4-oxo-quinoline-3-carboxylic acid) is a fourth-generation quinolone that has attracted the attention of chemists, as its pharmacokinetics and in vivo metabolism have been been thoroughly investigated (Vishwanathan, Bartlett, and Stewart 2002;Vu et al 2011;Sultana et al 2010;Xu et al 2010;Hemanth et al 2011). Raju et al (2012) recently determined the fragmentation pathways of moxifloxacin by electrospray ionization (ESI)-quadrupole ion trap mass spectrometry and ESI-quadrupole-time-of-flight (QTOF).…”
Section: Introductionmentioning
confidence: 99%